Resolving Species Identification and Distribution Patterns of Neotrygon spp. in Thai Waters: Inefficiency of Morphometric Analysis and the Power of COI Gene Barcoding and Phylogenetics - Panithanarak, Thadsin; Karuwanjaroen, Ratima; Utama, Chanapa; Laongmanee, Penchan; Meejan, Titirat; Senanan, Wansuk; Klangnurak, Wanlada; Khudamrongsawat, Jenjit; Krajangdara, Tassapon (My University, 2025)
Three species of maskrays in the genus Neotrygon have previously been reported in Thai waters. However, the high morphological similarity among species within the blue-spotted maskray complex (Neotrygon spp.) makes accurate identification challenging. This study aimed to confirm species identification in Neotrygon spp. using morphometric and genetic data and to further examine their phylogenetic relationships in Thai waters by analyzing mitochondrial COI (cytochrome c oxidase subunit I) sequences. Multivariate analysis (PCA) of 37 morphometric characters from 55 specimens proved insufficient for species-level discrimination. However, molecular phylogenetic analysis of 14 unique COI sequences from Thai waters, combined with 61 reference sequences from previously documented related species and closely related species, identified two monophyletic clades. These clades corresponded to two species: N. varidens, found exclusively in the Gulf of Thailand, and N. malaccensis, recorded for the first time in Thailand, occurring in both the Gulf of Thailand and the Andaman Sea. This DNA-based identification provides clear evidence for species boundaries within Thai Neotrygon species and highlights the importance of molecular tools for distinguishing morphologically similar marine species in the Indo-Pacific region.
Keywords: COI; Cryptic species complex; Gulf of Thailand; Molecular taxonomy; Neotrygon kuhlii